Dakriyosintigrafi ile alt ve üst kanaliküllerin gözyaşı drenaj aktivitelerinin değerlendirilmesi - (:unkn) unknown (My University, 2000)
AMAÇ: Bu çalışma, gözyaşı drenaj sisteminde alt ve üst kanaliküllerin rolünü ortaya koymak amacıyla yapılmıştır. YÖNTEM: Kanaliküllerin drenaj aktivitesinin ve kantitatif olarak gözyaşı akım hızının değerlendirilmesi amacıyla sırasıyla alt ve üst punktumlar kollajen tıkaçlar ile tıkandıktan sonra 12 olgunun 23 gözüne dakriyosintigrafi uygulandı. BULGULAR: Yirmi üç gözün 12'sinde üst kanalikülde, 11'inde alt kanalikülde hızlı drenaj saptandı. Alt ve üst kanaliküllerin drenaj hızları arasında istatistiksel olarak anlamlı farklılık tespit edilmedi (p>0.05) SONUÇ: Gözyaşı drenajında alt ve üst kanalikül birbirine yakın etkiye sahiptir.

PURPOSE: This study is carried out to assess the role of upper and lower canaliculi in the lacrimal drainage system. METHOD: in order to evaluate the drainage activity and the quantitative tear flow rates of the upper and lower canaliculi, dacryoscintigraphy was performed to twenty-three eyes of 12 volenteers after selectively occluding upper or lower canaliculi with collagen implant. RESULTS: In twelve of the 23 eyes, the upper canaliculi drained more effectively than the lower, in eleven eyes inferior canaliculi were more effective. No statistically significant difference was observed between the drainage activity of the upper and lower canaliculi (p>0.05). CONCLUSION: Upper and lower canaliculi are equally effective in lacrimal drainage system.
Assessment of the drainage acitivity of the upper and lower canaliculi by dacryoscintigraphy
Keywords: Biyoloji